Pemberdayaan Masyarakat Dalam Memahami Dan Mengoperasikan Alat Ukur Gps Geodetik - Ikhwanuddin Ikhwanuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The development of geospatial technology offers significant opportunities to enhance community knowledge, skills, and self-reliance in supporting the needs of the business sector. However, the utilization of Geodetic GPS remains limited due to insufficient knowledge and practical experience in applying modern geospatial technology. This community empowerment activity aims to improve participants’ knowledge and skills in spatial and elevation data surveying, topographic mapping, and the establishment of coordinate and reference elevation data (BM/benchmark) to support planning and construction activities. The activity was conducted on the premises of PT. Toya Indo Manunggal, Sekargadung Village, Pungging District, Mojokerto Regency, East Java. The methods included field preparation, control point installation, detailed topographic surveying using GNSS/Geodetic GPS with the Real-Time Kinematic (RTK) method, height-difference measurements using an Automatic Level, spatial data processing, and the preparation of digital topographic maps. The activity not only generated spatial data and topographic maps but also contributed to strengthening human resource capacity in understanding and applying geospatial technology. Through hands-on practice, mentoring, and the provision of appropriate technological facilities, this empowerment activity is expected to foster community self-reliance and enhance readiness to meet the increasingly technology-driven demands of the workplace and business sector.